Male-female earnings diffentials in Canada: where in the earnings distribution do they exist? - Mueller, Richard E. (Arts and Science, 2009)
The gender pay gap is the topic of countless papers in the economics and social science literature. Its study can be traced back at least as far as the Old Testament (Gunderson, 2006), and debates on the issue in the media and elsewhere often generate much more heat than light. For policy purposes, it is converse that is needed most. This research will use the SLID from 1996 and 2005 to determine (1) how the average gender pay gap has evolved over this decade, (2) if there are differences in the gender pay gap at various points of the pay distribution, and (3) if there have been changes in gender pay at these points in the pay distribution over this period. We “link” this current research with the previous Canadian literature on the subject using the ubiquitous Oaxaca-Blinder decomposition, followed by an extension of this technique which explicitly addresses the explained and unexplained part of the pay gap at different points along the pay distribution. We find that the adjusted mean hourly wage gap for females has increased about one percentage point between 1996 and 2005 to about 89 per cent of the male hourly wage. The wage gap differs depending on which range of the wage distribution is being considered, and is sensitive to the choice of wage measure.
Open access
Keywords: Gender pay gap; Wage gap; Pay distribution; Earnings differentials; Wages--Men--Canada; Wages--Women--Canada; Pay equity--Canada